Enteral nutrition support and treatment toxicities in patients with head and neck cancer receiving definitive or adjuvant helical intensity‐modulated radiotherapy with concurrent chemotherapy. Issue 2 (25th November 2022) - Blake, Claire L.; Brown, Teresa E.; Pelecanos, Anita; Moroney, Laura B.; Helios, Jennifer; Hughes, Brett G. M.; Chua, Benjamin; Kenny, Lizbeth M.
Abstract: Background: Enteral nutrition (EN) is often required in patients with head and neck cancer (HNSCC); however, initiation criteria is limited or inconsistent. This study aimed to describe the relationship of treatment toxicities and requirement for EN and investigate toxicity and baseline characteristics association with EN duration. Methods: Acute toxicities and baseline characteristics were collected from patients with HNSCC ( n = 110) undergoing H‐IMRT. Percentage EN contributing to estimated requirements and EN duration were measured. Results: The threshold for patients needing ≥50% of estimated requirements via EN increased from week 3 to 4 for grade ≥2 oral/pharyngeal mucositis, dysgeusia, thick saliva and nausea, and for grade 3 dysphagia. Patients with grade 2–3 dysphagia had a reduced risk of ceasing EN compared to those with grade 0–1 dysphagia. Conclusions: Using acute toxicities in clinical practice may be a useful tool to inform prompt initiation of EN prior to decline in nutritional status and anticipate EN duration.